2021
DOI: 10.1088/1742-6596/1879/2/022001
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Moringa oleifera seed extract on PbNP-Toxicity induced in rats

Abstract: This work was conducted to study the protective role of Moringa oliefera seeds extract (MSE) against the toxic effect of commercial lead nanoparticles (CPbNP) in rats. Twenty eight albino male rats were divided into four groups (seven animals in each one) as follow: (A) control group, (B) 160mg/kg body weight per day (b. wt./d.) of M. oliefera (MSE)seed extract, (C): 5mg CPbNP/kg b. wt./d. and (D): MSE + CPbNP. The experimental period was 45 days. Blood was drawn for protein and enzyme estimation at the end of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…[ 94,95 ] The toxicity of GO NPs has been fully confirmed in various cases, including oxidative stress and lipid peroxidation. [ 10–87 ] As a proposed mechanism to justify these observations, it can be suggested that the EAFE, due to its antioxidant properties, can neutralize free radicals caused by GO NPs and it has the ability to maintain oxidative homeostasis and combat oxidative stress in kidney, lung and testis tissues of mice. [ 96 ] Patlolla et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 94,95 ] The toxicity of GO NPs has been fully confirmed in various cases, including oxidative stress and lipid peroxidation. [ 10–87 ] As a proposed mechanism to justify these observations, it can be suggested that the EAFE, due to its antioxidant properties, can neutralize free radicals caused by GO NPs and it has the ability to maintain oxidative homeostasis and combat oxidative stress in kidney, lung and testis tissues of mice. [ 96 ] Patlolla et al.…”
Section: Discussionmentioning
confidence: 99%
“…[61] Al-Obaidi et al (2021) stated that lead nanoparticles (Pb NPs) decrease protein and albumin levels in the blood of mice, while M. oliefera seed extract improves blood protein and albumin levels. [73] 4.…”
Section: Cholesterol Triglycerides and Glucosementioning
confidence: 99%